2022
DOI: 10.1038/s41598-022-09917-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral intentions of rural farmers to recycle human excreta in agriculture

Abstract: Considerable progress has been made in developing human excreta recovery pathways and processes for maximum nutrient recovery and contaminant elimination. The demand segment has often been ignored as an area for future research, especially during the technology development. The findings from the few published articles on social acceptance show missing and inconclusive influence of demographic, sociological, and economic farmer-characteristics. This study endeavours to close this gap by using the social psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 89 publications
2
16
0
Order By: Relevance
“…Nevertheless, it is important to highlight that even when all barriers to reuse have been overcome, and any health risks arising from contaminants are mitigated for, risk perception remains a significant barrier to social acceptance of the reuse of resources in agriculture, with concerns in particular around the use of human excreta derived materials . Acceptance of resource reuse is limited by information and availability and therefore interventions are needed that focus on community specific social and behavior change communication that embraces coproduction of change with local farming organizations and members of the community . As a global community, we need to re-envisage what “waste” is to increase public acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is important to highlight that even when all barriers to reuse have been overcome, and any health risks arising from contaminants are mitigated for, risk perception remains a significant barrier to social acceptance of the reuse of resources in agriculture, with concerns in particular around the use of human excreta derived materials . Acceptance of resource reuse is limited by information and availability and therefore interventions are needed that focus on community specific social and behavior change communication that embraces coproduction of change with local farming organizations and members of the community . As a global community, we need to re-envisage what “waste” is to increase public acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…The TPB posits that individuals' conduct may be predicted based on their intentions, which are influenced by their attitudes and behavioural intents (Atta- Aidoo et al, 2022;Kangogo et al, 2021). These intentions, in turn, are shaped by social norms and the degree of control individuals perceive over their action (Gwara et al, 2022). The underlying premise of this perspective is that individuals' decision-making, choices, and behaviour are influenced by rational thinking, which is in turn shaped by three key factors: attitudes, subjective standards, and perceived behavioural control (Atta- Aidoo et al, 2022;Kangogo et al, 2021;Omotayo et al, 2020).…”
Section: Theory Of Planned Behaviour (Tpb)mentioning
confidence: 99%
“…Accordingly, a heightened inclination towards a behaviour, results in an improved intention to adopt certain agricultural technology which would enhance their household food-nutrition security (Outhwaite et al, 2022). Numerous research (Davis-Reddy, 2018;Gwara et al, 2022;Issahaku & Abdulai, 2020;Ren et al, 2018) have shown the significance of attitude in forecasting the inclination of farmers to embrace CSA practices. The influence of attitude on an individual's intention and behaviour has been recognized as a significant factor (Mullins et al, 2018).…”
Section: Theory Of Planned Behaviour (Tpb)mentioning
confidence: 99%
See 2 more Smart Citations